Introduction to this Volume: Applying Hedonics in the Swiss Housing Markets - Andrea Baranzini; José V. Ramirez; Caroline Schaerer; Philippe Thalmann (Swiss Journal of Economics and Statistics, 2008)
On June 27–30, 2007, we organized at the Geneva School of Business Administration an International Symposium entitled "Hedonic Methods in Real Estate". During the first day, called the "Swiss hedonic day", Swiss researchers from universities, consulting firms and banks discussed the models they use, the topics analysed, data, econometric issues, and results of the hedonic approach applied to the Swiss housing and property markets. We selected some of the papers that were presented during the Swiss Day, carefully reviewed them and had their authors revise them repeatedly. Those papers are now contained in the present issue of the Swiss Journal of Economics and Statistics. This contribution somehow summarizes the papers presented in this issue.
Keywords: R31; 330; Hedonic price indices; Switzerland; Housing Market